Technology and innovation in Japan : policy and management for the twenty-first century - Hemmert, Martin, 1964-; Oberländer, Christian (Routledge studies in the growth economies of Asia ;, 1998)
Long-awaited reforms in technology policy and corporate strategy are now taking place in Japan. This book asks whether it is the programme of reform or the will and ability to implement reforms which is new.